Peningkatan Akurasi Passing Pemain Futsal U-14 Melalui Model Latihan Terstruktur - Nurmilah Destina; Aprizal Fikri; Muslimin Muslimin; Dewi Septaliza (Performa, 2025)
This study aims to develop an effective and varied futsal passing accuracy training model for U-14 players that aligns with their developmental characteristics. The research employed the Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The final product consists of 20 training models utilizing simple equipment such as cones, grid boards, hula hoops, and water bottles, combined with audio-visual media to enhance motivation and technical understanding. The small-scale trial involved 15 athletes, while the large-scale trial involved 50 athletes from different futsal clubs. Validation by three experts indicated that the training model has high feasibility and practicality. The trial results showed an effectiveness level of 94.4% in the small-scale test and an average of 93.63% in the large-scale test. The study concludes that the developed training model significantly improves passing accuracy skills in U-14 players, is easy for coaches to implement, and serves as an effective guideline for developing basic futsal techniques